Exercise Regulates MicroRNAs to Preserve Coronary and Cardiac Function in the Diabetic Heart. Issue 11 (6th November 2020) - Lew, Jason Kar-Sheng; Pearson, James T.; Saw, Eugene; Tsuchimochi, Hirotsugu; Wei, Melanie; Ghosh, Nilanjan; Du, Cheng-Kun; Zhan, Dong-Yun; Jin, Meihua; Umetani, Keiji; Shirai, Mikiyasu; Katare, Rajesh; et al.
Abstract : Rationale: Diabetic heart disease (DHD) is a debilitating manifestation of type 2 diabetes mellitus. Exercise has been proposed as a potential therapy for DHD, although the effectiveness of exercise in preventing or reversing the progression of DHD remains controversial. Cardiac function is critically dependent on the preservation of coronary vascular function. Objective: We aimed to elucidate the effectiveness and mechanisms by which exercise facilitates coronary and cardiac-protection during the onset and progression of DHD. Methods and Results: Diabetic db/db and nondiabetic mice, with or without underlying cardiac dysfunction (16 and 8 weeks old, respectively) were subjected to either moderate-intensity exercise or high-intensity exercise for 8 weeks. Subsequently, synchrotron microangiography, immunohistochemistry, Western blot, and real-time polymerase chain reaction were used to assess time-dependent changes in cardiac and coronary structure and function associated with diabetes mellitus and exercise and determine whether these changes reflect the observed changes in cardiac-enriched and vascular-enriched microRNAs (miRNAs). We show that, if exercise is initiated from 8 weeks of age, both moderate-intensity exercise and high-intensity exercise prevented the onset of coronary and cardiac dysfunction, apoptosis, fibrosis, microvascular rarefaction, and disruption of miRNA signaling, as seen in the nonexercised diabetic mice. Conversely, the cardiovascular benefits of moderate-intensity exercise were absent if the exercise was initiated after the diabetic mice had already established cardiac dysfunction (ie, from 16 weeks of age). The experimental silencing or upregulation of miRNA-126 activity suggests the mechanism underpinning the cardiovascular benefits of exercise were mediated, at least in part, through tissue-specific miRNAs. Conclusions: Our findings provide the first experimental evidence for the critical importance of early exercise intervention in ameliorating the onset and progression of DHD. Our results also suggest that the beneficial effects of exercise are mediated through the normalization of cardiovascular-enriched miRNAs, which are dysregulated in DHD. Abstract : Supplemental Digital Content is available in the text.